Exercise- and diet-induced glycogen depletion impairs performance during one-legged constant-load, high-intensity exercise in humans - Martin Thomassen; Michael J. McKenna; Michael J. McKenna; Michael J. McKenna; Hugo Olmedillas; Victoria Wyckelsma; Jens Bangsbo; Nikolai Baastrup Nordsborg (Frontiers in Physiology)
IntroductionThe effect of muscle glycogen stores on performance during intense short-duration exercises in humans is unclear. We hypothesized that low initial muscle glycogen levels would impair constant-load intense one-legged knee extensor exercise lasting approximately 5 min and human muscle contractile function, as determined by maximal voluntary contraction (MVC), electrically induced single-twitch maximal force, rate of force development (RFD), and rate of relaxation. Furthermore, alter phosphorylation of the Na+/K+-ATPase (NKA) regulatory proteins AMPK and FXYD1 indicating attenuated NKA activity.MethodsWith one leg in a glycogen-depleted state and one leg in a glycogen-loaded state, ten healthy young males (age: 25 ± 2 years) performed three intense exercise trials including (i) two-legged cycling for ∼5 min and (ii) 2× one-legged knee extensor exercise to task failure. MVC determination, electrical muscle stimulation, blood sample testing, and vastus lateralis biopsies were performed to assess the muscle composition and function.ResultsTime to task failure during the one-legged knee-extensor exercise was reduced by approximately 40% (n = 10, P < 0.05) with exercise- and diet-induced glycogen depletion. At rest (n = 10), MVC, twitch force, RFD, and rate of relaxation were unaffected by glycogen content. After exercise to task failure, the single-twitch contractile characteristics were impaired to a greater extent (n = 10, P < 0.05) in the glycogen-loaded leg than in the glycogen-depleted leg, probably induced by longer exercise duration. Concomitantly, MVC (n = 10, except for 15 s: n = 5 and 8) was reduced to similar levels under both conditions. The exercise-induced increase in the nonspecific phosphorylation of FXYD1 (n = 10, P < 0.001), which regulates NKA activity, tended to be greater (n = 10, P = 0.06) in the glycogen-loaded legs, indicating augmented potassium handling.ConclusionExercise- and diet-induced low muscle glycogen content impairs high-intensity constant-load exercise performance lasting approximately 5 min. This was observed even with concomitantly better single-twitch contractile characteristics and similar reduction in MVC after task failure compared to glycogen-loaded legs. At rest, glycogen levels did not affect MVC and contractile characteristics.